2014
DOI: 10.5194/cp-10-1837-2014
|View full text |Cite
|
Sign up to set email alerts
|

Pliocene diatom and sponge spicule oxygen isotope ratios from the Bering Sea: isotopic offsets and future directions

Abstract: Abstract. Oxygen isotope analyses of different size fractions of Pliocene diatoms (δ 18 O diatom ) from the Bering Sea show no evidence of an isotope offset and support the use of bulk diatom species samples for palaeoceanographic reconstructions. Additional samples containing concentrations of sponge spicules produce δ 18 O values several per mille (‰) lower than δ 18 O diatom with a calculated mean offset of 3.9‰ ± 1.5. This difference is significantly greater than modern-day variations in water δ 18 O throu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The fractionation factor ( δ 18 O silica−seawater ) for the marine sponge (+36 to +39 ‰) was greater than that of freshwater sponges (+28 ‰) (Matteuzzo et al, 2013). The variation within the one individual from this study compares to an entire range of δ 18 O water of less than 0.8 ‰ and potential temperature variations of ∼ 5 • C across the Drake Passage (Meredith et al, 1999), and represents nearly half of the 5 ‰ variations found in a downcore sponge spicule δ 18 O record from Pliocene sediments (Snelling et al, 2014). The external spicules were consistently isotopically lighter than the internal interlocking spicules, although the difference between them (0.4 to 1 ‰) is approximately the same as the analytical error (2SD of 0.6 ‰).…”
Section: Oxygen Isotopesmentioning
confidence: 56%
See 2 more Smart Citations
“…The fractionation factor ( δ 18 O silica−seawater ) for the marine sponge (+36 to +39 ‰) was greater than that of freshwater sponges (+28 ‰) (Matteuzzo et al, 2013). The variation within the one individual from this study compares to an entire range of δ 18 O water of less than 0.8 ‰ and potential temperature variations of ∼ 5 • C across the Drake Passage (Meredith et al, 1999), and represents nearly half of the 5 ‰ variations found in a downcore sponge spicule δ 18 O record from Pliocene sediments (Snelling et al, 2014). The external spicules were consistently isotopically lighter than the internal interlocking spicules, although the difference between them (0.4 to 1 ‰) is approximately the same as the analytical error (2SD of 0.6 ‰).…”
Section: Oxygen Isotopesmentioning
confidence: 56%
“…Heating to higher temperatures of 80-90 • C is routine in downcore spicule opal δ 30 Si analyses (e.g. Snelling et al, 2014). …”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of amorphous biogenic silica (or opal) by photosynthetic diatoms, which play a major role in the export of organic matter to the seafloor, is a key part to both the cycling of silicon and carbon in the Earth's climate system (Tréguer and De la Rocha, 2013). Quantifying the dissolved silicon, or silicic acid (Si(OH) 4 ), concentration of upwelling waters is essential if we are to understand the distribution and growth of diatoms in surface waters and so the drawdown on atmospheric carbon dioxide (Hendry and Brzezinski, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A study of a marine carnivorous sponge δ 18 O showed large fractionation effects and highly heterogeneous isotopic behavior within one individual (Hendry et al, 2015). One downcore study indicates that there are systematic offsets between spicule and diatom bSiO 2 δ 18 O (Snelling et al, 2014).…”
Section: Oxygenmentioning
confidence: 99%